Life at oxygen minimum zone: bacterial symbiosis in the gills of the bivalve Kelliella miliaris - Utrilla, Olga; Viguera, Enrique; Gofas, Serge; Marina, Pablo; López-Téllez, Juan-Félix; Salas, Carmen (Frontiers in Marine Science, 2025)
Kelliella miliaris (Philippi, 1844) is a minute bivalve, living on the surface of soft sediments, from the continental shelf to bathyal depths, commonly in the oxygen minimum zones (OMZ) and/or in reducing habitats. The scarcity of data on the biology of Kelliella prompted us to investigate, at ultrastructural level, specimens found in southern Spain. Kelliella miliaris shows several morphological characteristics that would be adaptive for living in the OMZ: (1) presence of numerous muscular fibers in the mantle, mantle edge and gills-visceral mass connection; all of which would allow to actively move the gills and/or enable a better control of the ventral opening in relation to vertical movements of the animal; (2) high number (in relation to body size) and large size of gill filaments, mainly in the large inner demibranch; and (3) long cilia which would provide a large surface for capture of oxygen and a highly effective uptake of oxygen from water. We have observed in all the specimens examined the presence of numerous rod shaped bacteria among the gill cilia. These bacteria show the typical double membrane of Gram-negative bacteria. The analysis of the bacterial DNA revealed that Gammaproteobacteria is the most abundant class, with 53.69% of total reads. The latter, together with the peak of oxygen and the presence of sulfur inside the electron dense granules from the bacteria, determined by TEM-EDX analysis, point to the involvement of these bacteria in the oxidization of the sulfide to thiosulfate. The presence of bacteria in the gills of Kelliella miliaris highlights the importance of the chemosynthetic symbiosis in the OMZs of the oceans that has been probably overlooked up to now. The presence of different microorganisms in the stomach indicates heterotrophy. We have found spermatozoids inside the female gonad, which confirms internal fertilization in K. miliaris. However, the presence of protoconch I and protoconch II, indicates planktotrophic larval development.